PENERAPAN TRANSPARANSI DAN AKUNTABILITAS DESA DALAM MEMPERTANGGUNGJAWABKAN PENGELOLAAN KEUANGAN ALOKASI DANA DESA (ADD) DI DESA SUNGAI ABU, KECAMATAN AIR HANGAT TIMUR: H. EDWIN BUSTAMI, SE., MM - Edwin Bustami (JURNAL ADMINISTRASI NUSANTARA, 2019)
This research focuses on the application of the principle of transparency and accountability in the management of the Village Fund Allocation for the purpose of describing the management accountability Village Fund Allocation. This research was conducted because Allocation Fund Executive Team Village in performing its financial administration not in accordance with applicable regulations. This research is expected to be beneficial to the Kerinci district government, especially subdistrick Air Hangat Timur in an effort to increase management accountability Village Fund Allocation. This research was conducted in villages in Sungai Abu the sub district Air Hangat Timur, as one implementation location of the Village Fund Allocation. As the informant was elected Village Implementation Teams and the communities that are considered to represent the research unit in the management of the Village Fund Allocation. Research conducted in-depth interviews and direct observation by the implementation of the Village Fund Allocation. The results of this study indicate that for the planning and implementation activities of the Village Fund Allocation, has revealed the existence of management accountable and transparent. While accountability is seen in the physical results have shown the implementation of accountable and transparent, but from the administration still needed further development, because not fully in accordance with the provisions. The main constraint is not effective coaching village government officials and human resource competencies, so that still need assistance from local government officials on an ongoing basis